Emergency radiological evaluation of wandering spleen volvulus and infarction: A case report and review of literature - Muataz Kashbour, MBChB; Maaly Abuhlaiga, MBChB; Muhammed Asim Awan, MD; Khalid Gashoot, MD (Radiology Case Reports)
Wandering spleen (WS) is exceedingly rare and is attributed to the absence or maldevelopment of the spleen's anchoring ligaments. The diagnosis of WS in the emergency department poses a particular clinical challenge as the clinical presentation is highly variable from acute abdomen requiring immediate surgery to chronic indolent pain extending over years. Herein, we report the case of a 34-year-old nulliparous lady, who presented to the emergency department with left iliac fossa pain associated with vomiting, successfully diagnosed preoperatively using computerized tomography. A splenectomy was performed, and the patient achieved full recovery. Timely use of imaging aids emergency physicians in the early detection of wandering spleen. Early diagnosis allows spleen-preserving strategies and therefore prevents the life-threatening complications of postsplenectomy sepsis.